Emergence of Light-Transforming Layered Hybrid Halide Perovskites - AlSabeh, Ghewa; Milić, Jovana V. (WILEY-V C H VERLAG GMBH, 2026)
Layered hybrid halide perovskites (LHPs) have attracted considerable attention in optoelectronics. They are based on tailored organic spacer cations templating halide perovskite slabs, featuring improved stabilities compared to their 3D halide perovskite analogs. This has been especially relevant under functional optoelectronic device operating conditions, such as upon light irradiation, which has been associated with reduced ion migration that is responsible for material and device instabilities. The versatility of LHPs structures provides the opportunity to further enhance their functionality through light-induced transformations in hybrid materials and optoelectronic devices, setting the basis for multifunctional systems. The emerging class of such light-transforming layered hybrid halide perovskite materials is reviewed, outlining the challenges and perspectives for further development toward their application in (multi)functional opto(electro)ionic devices in the future.